Economic growth in the European Union: Exploring the role of innovation and gender - Coronel, Vicente J.; Díaz-Roldán, Carmen (Economics and Business Review, 2025)
This paper aims to investigate the linkages between human capital and employment in high-tech sectors and their impacts on economic growth, considering the overall level of innovation in both the public and private sectors and exploring the role of gender. The analysis employs dynamic ordinary least squares (DOLS) to estimate a model for the EU-27 across the period 2008–2021. The results indicate that employment in high-tech sectors is the variable that most contributes to economic growth in those countries that are leaders in innovation. However, in these countries, a positive and significant effect of the gender gap in employment is observed.